Peranan Web Desain dalam Internet - Bonafix, D. Nunnun (Humaniora, 2010)
Internet is an alternative media that have become a trend, a lifestyle and a need for people in the world. Moreover, the interface display of a website is getting more beautiful, more interesting, and more sophisticated. That's the reason why a web design presents a visual display of a website that has certain messages that cover layouts, graphic elements, and navigation systems to facilitate the users in browsing it. Now a website has shown the identity of a product, a company, and even the owner. To face a tight global competition, a web design plays an important role in surpassing other competitors.